Dynamic response of normal moving load on an irregular fiber-reinforced half-space. (January 2016) - Kaur, Tanupreet; Singh, Abhishek Kumar; Chattopadhyay, Amares; Sharma, Satish Kumar
Studying the problem of a moving load causing fracture is used in the interpretation analysis of geophysical fracture. This paper aims to study the stress produced in an irregular fiber-reinforced half-space due to a normal moving load on a free surface. The stress produced in this case has been obtained in a closed form. Three different cases of irregularity, viz. rectangular, parabolic and no irregularity, have been discussed and compared. The effects of depth, irregularity factor and maximum irregularity depth on stress have been investigated. Also, the stress produced from a normal moving load in an irregular isotropic half-space has been deduced as a special case of the problem and comparative study has been made with that of fiber-reinforced medium. Moreover, some important peculiarities have been depicted with the use of graphs.